A COMPARATIVE EVALUATION OF ANTI-DIABETIC POTENTIALITY FOUND IN DIFFERENT MARKETED POLYHERBAL FORMULATION USING GLUCOCORTICOID-INDUCED HYPERGLYCAEMIA IN RABBIT - Boruah, Pranjal; Chakraborty, Jashabir; Dash, Suvakanta (International Journal of Current Pharmaceutical Research, 2017)
Objective: The aim of this study was performed to evaluate Antidiabetic potentiality found in different marketed polyherbal formulation using glucocorticoid-induced hyperglycaemia in the rabbit. Methods: The potentiality of different polyherbal formulation was investigated using dexamethasone (DEX) induced hyperglycaemia in Rabbit. Eight male rabbits were divided into four groups of two each. The first group is regarded as control group received 3 ml of normal saline daily by using the gastric tube for 15 d and remaining three group received (0.35 mg/Kg B.W. single dosage) of dexamethasone tablets which were powdered, dissolved in 3 ml of normal saline daily for 15 d. After 15 d the blood glucose estimated by using a glucometer and it is found that DXE treatment leads to significant increase in levels of glucose and a significant decrease in body weight. After that second group received metformin tablet. The third and fourth group received polyherbal formulation A and formulation B, which are powdered and dissolved in 3 ml of normal saline daily for 15 d at the dose of 0.5 gm/kg body weight orally. After completion of regular administration for 15 d, the blood glucose was again estimated and compare the results of each the group. Conclusion: The Anti-diabetic polyherbal marketed formulations were having less side effect as compared to standard metformin tablet (e. g. body weight loss). And both the polyherbal formulations were found a therapeutic equivalence to each other, also having the approximately similar potentiality to standard metformin tablet. Results: The result was found that the polyherbal marketed formulations were having less side effect as compared to standard metformin tablet (e. g. body weight loss). And both the polyherbal formulations were found significantly decreased in blood glucose level at equal potentiality, which can be consider as therapeutic equivalence to each other, and both the formulation also having the approximately similar potentiality to standard metformin tablet. Â 